Prevalence of Antisocial Behavior among Secondary School Students in Nairobi City County - Ndehi, Violet; Ndung'u, Elijah; Nyagah, Virginia (International Journal of Psychology, 2023)
Purpose: The aim of this study was to determine how common antisocial behavior is among secondary school students in Nairobi City County. Methodology: The study employed a parallel convergent mixed-method design with a target population of 38,641 adolescents, parents, and teachers in Nairobi County secondary schools. Quantitative Data was collected from 398 adolescents in forms 2 and 3 via random sampling. All school categories were represented through cling cluster sampling, while simple random sampling selected respondents within each school. Qualitative data was purposively obtained from 10 students, 10 parents, and 10 teachers. Proven psychometric tools like Assessment of identity Development in Adolescence, Strengths and Difficulties Questionnaire, Children's Perception of Inter-Parental Conflict Scale, and Dhaka Stress Scale-Adolescent collected quantitative data. Pearson coefficient correlations were calculated using Statistical Package for Social Sciences (SPSS version 25) to explore relationships between variables. Findings: Based on this analysis, this study revealed the prevalence of moderate to severe antisocial behaviour in at least half of the adolescents in Nairobi. This is, however, not unique to the county. In attempting to explain the causes of antisocial behaviour among adolescents using the Problem Behaviour Theory by Jessor, et al. (2004), many scholars have witnessed it as a worldwide phenomenon. Unique Contribution to Theory, Practice and Policy: The study recommended for the involvement of counselling professionals in the screening and treatment. The Ministry of Education must also undertake the task of harmonizing the school curriculum. By doing so, the curriculum can be developed into a well-balanced and comprehensive framework that promotes a healthier learning environment for students.